Development of Assessment Instruments in Project-Based Learning to Measure Students Scientific Literacy and Creative Thinking Skills on Work and Energy Materials - Rosidin, Undang; Herliani, Dwi; Viyanti (Postgraduate, University of Mataram, 2023)
This study aims to develop a project-based learning assessment instrument to measure scientific literacy and students creative thinking skills on work and energy material that is valid, reliable, and practical to use. The method used is Research and Development (R&D) using 7 development steps adapted from Borg & Gall (1989). The results of the expert validation of the scientific literacy skills assessment instrument and students creative thinking skills were declared valid with a very high category. In the results of the data test analysis, there were 20 questions on the scientific literacy ability instrument and 18 questions on the creative material of the thinking ability instrument which were declared valid. Meanwhile, in the practicality test, this assessment instrument obtained very high criteria. based on the results that have been obtained, the final product is a project-based learning assessment to measure students’ scientific literacy and creative thinking abilities in the developed business and energy material that meets the eligibility standards of the instrument, that is valid, reliable and practical.